2023
DOI: 10.3390/molecules28031449
|View full text |Cite
|
Sign up to set email alerts
|

Co-Encapsulation of Drugs for Topical Application—A Review

Abstract: Achieving the best possible outcome for the therapy is the main goal of a medicine. Therefore, nanocarriers and co-delivery strategies were invented to meet this need, as they can benefit many diseases. This approach was applied specifically for cancer treatment, with some success. However, these strategies may benefit many other clinical issues. Skin is the largest and most exposed organ of the human body, with physiological and psychological properties. Due to its exposition and importance, it is not difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 126 publications
0
2
1
Order By: Relevance
“…Similarly, in our study we have noticed the 2C5-modified nanopreparation to be safer than the DOX. Earlier studies have shown severe dermatological toxicities even with liposomal DOX treatment [32] however, in our 2C5 modified nanoparticle preparation we have observed none of these dermatological toxicities. Nonetheless, we observed such dermatological toxicities in the free drug (DOX) group alone.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, in our study we have noticed the 2C5-modified nanopreparation to be safer than the DOX. Earlier studies have shown severe dermatological toxicities even with liposomal DOX treatment [32] however, in our 2C5 modified nanoparticle preparation we have observed none of these dermatological toxicities. Nonetheless, we observed such dermatological toxicities in the free drug (DOX) group alone.…”
Section: Discussioncontrasting
confidence: 77%
“…In comparison to chemical penetration enhancers, nanoparticles have a number of benefits, including continuous medication release over an extended length of time and preservation of encapsulated compounds against chemical deterioration. The carrier must release the encapsulated medicine so that it may be absorbed via the skin layers and disease-related subcutaneous tissues for the best topical drug administration into the skin [ 101 ].…”
Section: Barrier In Skin and Nanoparticles (Nps) As Delivery Agentsmentioning
confidence: 99%
“…On this basis, co-delivery of other chemotherapeutic drugs or natural active products also achieves synergistic therapeutic effect [ 53 ]. Chao and co-workers reported a mesoporous magnetite ferrite NP as an inorganic drug carrier, which can efficiently encapsulate hydrophobic drug (rifampin) and simultaneous co-load hydrophilic drug (isoniazide) [ 54 ].…”
Section: Co-delivery System In Medical Fieldmentioning
confidence: 99%